Strengthening Village Youth Leadership Competencies through Participatory Training Models and Community-Based Discussion Forums - Supriadi Supriadi; Adhitya Rizky Arissaputra Aswanto; Mohammad Nasir; Moh Irwan; Arini Zulfaidah; Indri Triawati (Universitas Kristen Cipta Wacana, 2025)
Limited civic literacy capacity and weak village community governance remain significant challenges to strengthening community participation in various rural areas of Indonesia. This situation was also found in Duko Village , Arjasa District , Sumenep Regency , which is characterized by low understanding among officials and the community regarding digital literacy, village profile documentation, and participatory governance practices. This community service activity aims to increase civic literacy capacity and strengthen community governance through structured and collaborative mentoring. The implementation method uses a participatory action approach, including needs assessment , citizenship and digital literacy training, assistance in preparing village profiles, and facilitating improvements to community governance mechanisms. The results of the community service show a significant increase in the community's ability to compile and update village profiles, an increased understanding of substantive citizenship values, and the formation of more focused coordination and accountability practices within village organizations. The implications of this activity confirm that a mentoring model based on participation, literacy, and cross-stakeholder collaboration can be an effective strategy in strengthening community capacity and supporting sustainable village development.